Saint-Exupéry Et La Question Des Relations Humaines : Une étude de Vol de Nuit et Terre des Hommes - Gli, Mawuyra (European Scientific Journal, ESJ, 2018)
Man is by nature a gregarious being. He is a member of a community in which human beings are in constant confrontation. He has various connections with members of his community. Because of the fundamental nature of what is at stake, his relationship with other members is at the same time a source of cohesion and conflict. On the one hand, it unites (or binds) the subjects of the global society and contributes to their fulfillment. But on the other hand, it can be a source of tension and conflict between actors or agents, individual or collective. The present study aims at analyzing the importance of human relations as conceived by Saint-Exupéry in two of his narrative texts: Vol de Nuit (Night Flight) and Terre des Hommes (Wind, Sand and Stars). Based on the hypothesis that the relationship that human beings maintain among themselves can contribute favorably to their development, the study further seeks to expose the importance and implication of human relations in the texts of Saint- Exupéry. This study is in the domain of humanism (a theory or doctrine which takes as its end the human person and his development). The study demonstrates to what end the phenomenon of human relations is evoked in the two narrative texts. This will undoubtedly lead us to understand the reflections Saint-Exupéry presents in his texts. The study is based on textual data collected from the two texts. It is hoped that this paper would help readers better appreciate the question of human relationship as an aspect of the author’s humanist persuasion.